EFFECTS OF DEFORESTATION ON GLOBAL WARMING AND CLIMATE DISRUPTION IN MANIEMA PROVINCE: THE CASE OF THE CITY OF KINDU - Kungwa Kahozi Etienne; Munga Baraka Stéphane; Kyanga Kituka Giscard; Musenge Jean De Dieu; Et Bambalati Sabiti Janvier (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2025)
In Maniema Province, especially in the city of Kindu, deforestation has major effects on warming and local climate disruption. The continuous loss of forest cover reduces the area’s ability to absorb carbon dioxide, which contributes to rising temperatures. The reduction of vegetation also alters atmospheric humidity and disturbs rainfall patterns, making seasons increasingly unpredictable. These changes lead to more frequent extreme weather events, such as heavy rainfall, sudden floods, drought periods, and heatwaves. In Kindu, deforestation further contributes to soil erosion, the degradation of agricultural land, and an increased risk of flooding. This situation directly affects biodiversity, local economic activities, and the living conditions of the population. Therefore, implementing reforestation actions and sustainable forest management is urgently needed.